IMPLEMENTASI SMART BUILDING SYSTEM PADA PENGENDALIAN UTILITAS PENCAHAYAAN DAN SUHU RUANG BERBASIS IOT - Aqilah Auliana Syahrifah; Eko Suwarno; Ariffa Rahayu; Arsyad Agus Al Muzammil; Artha Vanja Saktiya; Hartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Internet of Things (IoT) technology has encouraged the implementation of smart building concepts in building utility management to improve energy efficiency and indoor comfort. This study aims to implement an IoT-based smart building system for automated lighting and room temperature control. The research employed a quantitative descriptive method through system implementation and performance testing by measuring lighting intensity, room temperature, and electrical energy consumption in real time. The system was designed using light and temperature sensors integrated with a microcontroller and a cloud-based monitoring platform. The results indicate that the system maintained an average lighting level of 285 lux in accordance with SNI 03-6575-2001 standards and stabilized room temperature within the range of 24–25°C. The implementation also achieved energy savings of 22% compared to manual operation, with a system response time of approximately 5–7 seconds. These findings demonstrate that IoT-based automation can enhance environmental stability while optimizing building energy usage. This study contributes to the development of IoT-based building utility automation supporting smart and sustainable building concepts